The structure of the pharmaceutical market in Iran using concentration indices - Mohammad Mohseni, (Electronic Physician, 2017)
Background and objective: The efficiency and function of the pharmaceutical sector, as a vital portion of the health system, have a significant effect on intermediate and final indices of health. In this research, the structure of the pharmaceutical market in Iran was examined through the calculation of concentration indices in 2011. Methods: In this cross-sectional study, the needed data was gathered from the Food and Drug Administration in the year 2011. Data were analyzed using SPSS software version 20 and Microsoft Office Excel software. Finally, two common measures of market concentration, the Concentration Ratio and the Herfindahl-Hirschman Index, were calculated. Results: The largest and the smallest shares of the industry were 5.57% and 0.01%, respectively. The average industry share was 1.09%. The share range was calculated to be 5.56%. The Herfindahl-Hirschman Index was 248.5, which indicates a very low concentration of the pharmaceutical market in Iran. Also, based on the Concentration Ratio of 4 companies (18.39%), the concentration of the pharmaceutical market has been too low. Conclusion: The pharmaceutical market in Iran has a very low concentration and it does not have an exclusive mode in terms of market structure. Therefore, it can be attributed to the competitive model. The policy makers in this area can use this characteristic as a leverage to improve efficiency, fairness, revenue and health indices